2000
DOI: 10.1002/1098-1004(200009)16:3<211::aid-humu4>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

A deletion distinct from the classical homologous recombination of juvenile nephronophthisis type 1 (NPH1) allows exact molecular definition of deletion breakpoints

Abstract: Juvenile nephronophthisis, an autosomal recessive cystic kidney disease, is the most common genetic cause of end‐stage renal disease in children and young adults. We recently identified by positional cloning the causative gene, NPHP1. Its gene product nephrocystin may play a role in focal adhesion and adherens junction signaling. Approximately 80% of all patients with NPH1 carry large homozygous deletions, which contain the NPHP1 gene. These common deletions are positioned within a complex arrangement of large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 41 publications
(59 reference statements)
1
11
0
Order By: Relevance
“…2). None of these sequences are known to predispose to genomic rearrangements, although short stretches of identical sequence are often found at the sites of germline translocation and deletion breakpoints [20-22]. Genomic analysis of the parents and siblings of Case 2 indicated that the mutation was sporadic.…”
Section: Resultsmentioning
confidence: 99%
“…2). None of these sequences are known to predispose to genomic rearrangements, although short stretches of identical sequence are often found at the sites of germline translocation and deletion breakpoints [20-22]. Genomic analysis of the parents and siblings of Case 2 indicated that the mutation was sporadic.…”
Section: Resultsmentioning
confidence: 99%
“…The most notable structural feature is a Src homology 3 (SH3) 2 domain, a widespread protein-protein interaction module recognizing proline-rich motifs, which spans residues 157-207 of human nephrocystin. Another structural feature predicted from the nephrocystin amino acid sequence is a series of three 17-18-residue stretches, all within the N-terminal 105 amino acid residues, predicted to form short coiled-coil domains (7,8). The coiled-coil domain is an amphipathic ␣-helical heptad repeat recognized for its ability to mediate protein dimerization or oligomerization through hydrophobic interactions (9).…”
mentioning
confidence: 99%
“…In addition to human, cDNAs encoding full-length mouse nephrocystin have been described (7,8), as has a partial cDNA for canine nephrocystin (7). Comparison of the human and mouse sequences indicate that the N-terminal region of predicted coiled-coiled domains and the nearby SH3 domain are well conserved, with each showing 80% amino acid identity.…”
mentioning
confidence: 99%
See 2 more Smart Citations